Relative Validity and Utility of a Short Food Frequency Questionnaire Assessing the Intake of Legumes in Scottish Women - Papadaki, A.; Scott, Jane (Wiley-Blackwell Publishing Ltd., 2007)
Objective To validate a five-item, semi-quantitative, short food frequency questionnaire (SFFQ) designed to estimate daily legume consumption over a week, against results obtained from 7-day food diaries (7-day FD). Design Participants completed a 7-day FD and at the end of this period completed the SFFQ, to indicate the number of times they ate five legume-containing dishes in the previous week and what size portion of each dish they consumed. Daily legume intake (g day)1) was calculated for both methods and participants were classified into tertiles of intake for each method. Subjects/setting Fifty-one healthy females aged 25–55 years, employed at the University of Glasgow, Scotland, UK between May 2003 and December 2004. Results The two methods produced a similar mean intake of legumes [SFFQ: 14.8 (95% CI: 9.9–19.8) versus 7-day FD: 14.9 (95% CI:9.3–20.6) g day)1] and the Pearson’s correlation coefficient was 0.353 (P = 0.038). Exact agreement within tertiles and gross misclassification were 54.9% and 9.8% respectively. The weighted kappa statistic indicated fair agreement between the two methods (j = 0.262). Conclusions The SFFQ is an acceptable instrument for estimating legume consumption over a week and can be used to rank individuals according to the intake of this food group in similar nutrition intervention studies.